Maximum undergrounding degree of HV subtransmission networks as dictated by unscheduled power flows - Lauria, Stefano; Palone, Francesco (IET generation, transmission & distribution, 2013)
Meshed HV subtransmission networks are subject to undesirable parallel (unscheduled) active power flows from the EHV system. The phenomenon is worsened by conversion of HV overhead lines to underground cables (UGCs), which increases parallel flows through the HV network because of the attendant reduction in HV line reactance; the effect increase with network extension and are compounded by UGC charging power. The study deals with the assessment of the maximum undergrounding degree for a given subtransmission network. An analytical formulation of maximum HV line extension length as a function of EHV power flow and undergrounding degree is given; optimum UGC shunt compensation requirements are evaluated. Application to a typical 150 kV–50 Hz network is presented, showing a very good agreement with power flow simulation. In particular, the case study evidences that complete undergrounding of the HV network is possible if line length is under 50 km; the proposed shunt compensation effectively raises this limit to 70 km.